The effect of syngas addition on flameless natural gas combustion in a regenerative furnace (2022)
ABSTRACT: The present work numerically and experimentally studies the mixture of 30% syngas and 70% natural gas (SG-NG), by volume, and compares performance to pure natural gas (NG). The experimental measurements were carried out in a semi-industrial regenerative furnace originally designed for pure natural gas. A 25 kW thermal input and a 1.2 excess air ratio were maintained throughout. Temperatures and species were measured inside the combustion chamber. The effect of the syngas on the reaction zone location was determined by imaging spontaneous chemiluminescence. The effect of preheating was also studied for the SG-NG mixture. CFD modeling was used to analyze the effects on recirculation patterns. SG-NG exhibited an average temperature decrease of 6% compared to NG, due to the greater recirculation and increased CO2 in the flue gases. The species uniformity remained consistent, while the thermal uniformity factor (RTU) decreased by 10.5%, indicating greater uniformity. NOx emissions decreased by almost 50% for the SG-NG mixture. The addition of syngas improved the reactivity and displaced the reaction zone upstream. Without preheating, the recirculation and the reactant dilution decrease, generating a disturbance in the thermal uniformity (RTU increase by 65%) and the reaction zone was displaced downstream.